Sono-enzymatic programmable hydrogel enables spatiotemporal-controllable embolization with integrated tri-modal intra-/postoperative monitoring - Yang Sun; Honggang Shi; Jiayi Jiang; Feile Ye; Xinxi Yu; Chuandong He; Kun Liu; Xianglong Zhong; Pan Lu; Shengchao Zhao; Yanlv Chen; Menghui Liu; et al. (Chemical Engineering Journal, 2026)

Analytical solution for seismic response of deep parallel tunnels under inclined P/SV waves - Xinxi Li; Haitao Yu (Soil Dynamics and Earthquake Engineering, 2026)

Advanced functional epoxy reinforcement framework for flame-retardant phase change materials toward battery thermal runaway mitigation - Qiqiu Huang; Jian Deng; Xinxi Li; Yuhang Wu; Weifu Xu; Chen Fang; Guanxun Diao; Lizhong Yang; Jun Ren; Ziyu Huang; Yu Zhang; Haojing Wang; et al. (Chemical Engineering Journal, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Mulberry leaf extract improves non-specific immunity and antioxidant capacity of largemouth bass (Micropterus salmoides) fed a high-starch diet - Jing Tingsen; Luo Hui; Huang Junwa; Li Zhe; Li Yu; Jin Honghao; Zou Xinxi; Ke Zhenlin; Sun Wenbo; Hou Mengdan; Yang Huijun; Ye Hua (Frontiers in Marine Science, 2022)
A 70-day experiment was conducted to investigate the effects of mulberry leaf extract (MLE) on growth, proximate compositions, antioxidant and plasma biochemical parameters, and indices of non-specific immunity of largemouth bass ( Micropterus salmoides ) fed a high-starch diet. Two hundred eighty largemouth bass (initial body weight, 68.00 ± 0.19 g) were randomly fed seven diets: basal-starch diet (BSD; 8.88% starch), high-starch diet (HSD; 11.42% starch), and HSD diets supplemented with 0.05%, 0.10%, 0.20%, 0.50%, and 1.00% MLE (MLE1, MLE2, MLE3, MLE4, and MLE5, respectively). The results indicated that HSD and MLE did not significantly affect the growth performance of largemouth bass during the experimental period compared with that of the BSD, but the supplementation with more than 0.20% (MLE3, MLE4, and MLE5) MLE significantly decreased the hepatosomatic index (HSI) values, and 1.00% (MLE5) MLE significantly decreased the viscerosomatic index (VSI) values. The whole-body moisture of fish fed an HSD decreased significantly, while the whole-body lipid content increased significantly in the HSD group compared with the BSD group. Compared with HSD, MLE supplementation significantly decreased the moisture and lipid contents in the whole body. Supplementation with more than 0.20% MLE (MLE3, MLE4, and MLE5) significantly decreased the moisture content in the muscle. Supplementation with 1.00% MLE significantly decreased the content of hepatic and muscle glycogen. The malondialdehyde (MDA) content of the HSD group was significantly increased compared to that of the BSD group, whereas more than 0.10% (MLE2, MLE3, MLE4, and MLE5) MLE significantly decreased the MDA content. Additionally, the total antioxidant capacity (T-AOC), catalase (CAT), and glutathione peroxidase (GSH-Px) activities of MLE5 were significantly higher than those of the HSD group. The complement-3 (C3) content and globulin (GLB) in the plasma of the HSD group were significantly lower than those of the BSD group. Plasma C3 levels in the MLE3, MLE4, and MLE5 groups were significantly higher than those in the HSD group. In addition, glucose (GLU) levels in the MLE3, MLE4, and MLE5 groups were significantly lower than those in the HSD group. Supplementation with 0.50% (MLE4) MLE significantly increased the lysozyme (LYZ) content and decreased the activities of alanine transaminase (ALT) and aspartate transaminase (AST). Supplementation with 1.00% MLE significantly increased complement-4 (C4) and GLB contents and alkaline phosphatase (ALP) activity. Overall, these findings suggest that MLE could improve antioxidant capacity, immune function, and glycolipid metabolism, thereby alleviating the negative effects of a high-starch diet in M. salmoides .

Analysis of iron composite flow in China - Xinxi Chen; Jiansu Mao; Guangjie Yu (Environmental Science and Pollution Research, 2022)

Study on mechanical properties and energy characteristics of carbonaceous shale with different fissure angles under dry–wet cycles - Xinxi Liu; Yu Li; Weiwei Wang (Bulletin of Engineering Geology and the Environment, 2022)